ELECTRICAL CONDUCTIVITY OF MUSCOVITE AT HIGH TEMPERATURES - Guseynov A.A.; Batyrmurzayev A.S. (My University, 1989)
We investigated the temperature dependence of electrical conductivity in the muscovite group, the most widespread type of mica. The octahedra make the key contribution to the structure and properties of mica. A brief description of the minerals that we studied is given. Our experimental results and published data lead to the following conclusions. The crystallization is accompanied by ordering of the octahedral cation, giving rise to order in the coordination spheres of the tetrahedral layer of mica and of the interlayer cations and additional anions. This ordering slows the increase in conductivity, or even causes it to decrease in the temperature interval under consideration. Muscovite from metamorphic pegmatite segregations contains more iron than muscovite from igneous pegmatite. Therefore, the fact that the prominence of the conductivity anomaly depends on the iron content can be used as a diagnostic sign for the origin of the muscovite.